ASSOCIATION BETWEEN THE USE OF LEGAL SUBSTANCES IN UNIVERSITY STUDENTS: AN INTEGRATIVE LITERATURE REVIEW - Miranda, Kézia Auriene Teixeira; Souza, Katiane de Castro Guimarães; Miranda, Gabriela Gonçalves; Cardoso, Mirele Pinheiro; Vaz, Samara Alves (CIPEEX, 2025)
The use of legal substances among university students has become a public health problem. These students are more prone/susceptible to developing diseases, premature death, and addiction. The objective is to analyze the relationship between the use of legal substances among university students. This is a literature review developed from bibliographic material obtained from databases such as Scielo, Lilacs, PubMed, and BVS. Data collection involved a thorough analysis of the literature to obtain a complete understanding of the topic. The results obtained through this research highlight that this study scenario reveals a worrying reality that affects the health and lives of university students. After reaching the end of this study, it is clear that, unfortunately, the increase in the use of these legal substances is a common problem among academics from different universities and has affected more and more students.